Relationship between internet use and selected dimensions of positive youth development - Joorabchi, Toktam Namayandeh (2013)
The importance of public use of the Internet has noticeably increased in our daily lives. The Internet, with its imminence potential possibilities, has been a major attraction, especially for students because they are often involved with the Internet based on the need for accessing information, satisfying leisure activities, transferring information, and communicating with others near and far in real time. This study was designed based on the application of Media System Dependency and Uses and Gratification theory to understand Internet usage among students. The objectives of this study are to identify the relationships between the pattern of Internet usage, attitude towards the Internet, Internet skills, problems and purpose of using the Internet with the gratification of Internet usage as mediation and selected dimensions of positive youth development. The present study used a survey design to achieve its objectives in which cluster sampling was employed. A total of 400 respondents participated from Universiti Putra Malaysia in this study to analysis the data SPSS version (19) and AMOS version (18) were the statistical tools used in this study. Five categories of gratification for using the Internet were identified, namely, Escape, Affective, Cognitive, Social Integration, and Personal Integration. In addition, four selected categories of positive youth development were identified in the current research which is confidence, character, caring, and connection. Most students use the Internet to search for and get knowledge. They think that the Internet is the fastest way to research knowledge and they have a positive attitude toward the Internet. This research found that checking Facebook was the most important purpose for students to use the Internet. This study also found that most popular search engine is Google.com. The most common problem of using the Internet is slow Internet connection and the most common gratification of using the Internet is searching for information. This study found that there was significant relationship between problem of using Internet and connection in PYD dimension. There was also significant relationship between attitude and character. In addition, there was significant relationship between attitudes toward the Internet and gratification of Internet use. Furthermore, the relationship between purpose of Internet usage and connection was also significant. Finally this study found that the relationship between purpose of using Internet and gratification was significant. Meanwhile, the results show that there was no significant direct relationship between Internet skill and the four dimensions of positive youth development and gratification of Internet usage. The results also indicate that there was no significant direct relationship between years of using the Internet and four dimensions of positive youth development. In addition, there was no significant relationship between pattern of Internet usage and gratification of Internet usage. However, the results found that there was significant direct relationship between gratification of Internet usage and the four dimensions of positive youth development.